Use of Manganese in RT-PCR Eliminates PCR Artifacts Resulting from DNase I Digestion - P. Bauer; A. Rolfs; V. Regitz-Zagrosek; A. Hildebrandt; E. Fleck (BioTechniques)
The precise quantification of rare mRNA copies from intronless genes by reverse transcription polymerase chain reaction (RT-PCR) requires the complete removal of genomic DNA because discrimination of cDNA and DNA amplification products by differing sizes of PCR products is not possible. Elimination of DNA is achieved by treating the RNA sample with RNase-free DNase I before RT-PCR. The lack of a PCR product from DNase-treated RNA samples before RT is usually accepted as a proof of efficient DNA destruction. However, this may vary depending on the metal cofactor used in the DNase I cleavage. Treating DNA-contaminated RNA samples with DNase I and magnesium as a cofactor creates a negative PCR control after digestion without further RT. Paradoxically, after additional RT-PCR, the original intron-containing DNA fragment size may be produced again. In the presence of manganese as cofactor, RT-created DNA fragments do not appear. This is because in the presence of manganese, DNase I cleaves both DNA strands at approximately the same site, yielding DNA fragments that are blunt-ended or that have protruding termini of only one or two nucleotides in length. However, overlapping fragments with the potential to recombine are created by DNase digestion with magnesium as cofactor. Because one cannot differentiate between a PCR signal produced by RNA and one produced by recombined DNA after DNase I digestion and RT, all such DNase I assays should be performed with manganese instead of magnesium.